BORROWINGS FROM EUROPEAN LANGUAGES IN THE RUSSIAN LEXICON (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
Borrowings from European languages constitute an important part of the Russian lexical system. Throughout history, political, cultural, and economic contacts between Russia and European countries led to the adoption of numerous foreign words into Russian. These borrowings enriched the vocabulary by introducing new concepts in science, technology, culture, and everyday life. The article analyzes the historical stages of European lexical borrowings in Russian, their sources, semantic fields, and adaptation processes. Special attention is given to German, French, English, Dutch, and Italian influences and their role in the development of modern Russian vocabulary.